Tédio e apatia como sintomas: manejos na clínica psicanalítica - Gradin, Adriana Meyer Barbuda (2018)
This research starts from the objective of deepening theoretical and clinical thinking about boredom and apathy, symptoms that have been reported in analysis in an increasingly significant number, both by young people, and by adults and children who experience an anesthetized existence, unmotivated and without pleasure; also starts from the enigmas and obstacles experienced in psychoanalytic clinic and aims to group knowledge about boredom and apathy, in order to propose an instrument of clinical management for cases of psychic suffering of individuals marked by such symptoms. It has, therefore, the nature of a psychoanalytic research, of theoretical-clinical order. From the listening of such cases, it is proposed in this work a classification of the manifestations of boredom and apathy, a choice that is made not by ode to the theory, but rather, with the intention of finding subsidies to differentiate each manifestation of the others in order to reflect on the possible clinical management. The appreciation of the symptoms of apathy and boredom is made from some vignettes and clinical cases. In the dissertation, it is also appreciated the performance of the analyst against such impasses. It seeks to understand how analytical management can enable a route of symbolization and access the ability to be alive to the bored or apathetic pacient. It is argued that, in such cases, the analyst should offer a space not only for deciphering verbal contents to meet the purposse of making que repressed material conscious, but, more broadly, to offer a space of continence of nonverbal aspects and forms of unconscious communication. It is maintained that clinical listening of boredom and apathy requires the analyst to adopt an ethics of care: the analysis must be a potential space that can enable an amplification of the analysand's capacity to represent his traumas and psychic pains that had to be silenced; a space that produces a fruitful encounter as well as the work of mourning of the analysand and his works of play and dreaming, so that he can invest in objects and recognize otherness in a non-threatening way